2022
DOI: 10.3389/fimmu.2022.847894
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD39 in COVID-19 Severity: Dysregulation of Purinergic Signaling and Thromboinflammation

Abstract: CD39/NTPDase1 has emerged as an important molecule that contributes to maintain inflammatory and coagulatory homeostasis. Various studies have hypothesized the possible role of CD39 in COVID-19 pathophysiology since no confirmatory data shed light in this regard. Therefore, we aimed to quantify CD39 expression on COVID-19 patients exploring its association with severity clinical parameters and ICU admission, while unraveling the role of purinergic signaling on thromboinflammation in COVID-19 patients. We selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…Interestingly, Wang, Veurich, Kalbasi, Graham, et al ( 2021 ) identified increased CD39 expression in the lung, liver, spleen, and PBMCs from severe COVID‐19 patients, which correlated with days in the hospital, days in intensive care unit (ICU), and markers of coagulation, indicating associations between ectonucleotidases and disease progression. Similarly, CD39 messenger RNA (mRNA) as upregulated in peripheral blood leukocytes in association with higher soluble CD39 levels in severe COVID‐19 patients, which were related to the length of hospital day and ICU admission (Díaz‐García et al, 2022 ). Furthermore, upregulation in CD39 expression in late‐stage COVID‐19 was associated with heightened levels of STAT‐3 and HIF‐1α, but decreased levels of CD39‐antisense RNA, possibly a purinergic imbalance that contributes to metabolic changes and T‐cell dysfunction (Wang, Veurich, Kalbasi, Shaefi, et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Wang, Veurich, Kalbasi, Graham, et al ( 2021 ) identified increased CD39 expression in the lung, liver, spleen, and PBMCs from severe COVID‐19 patients, which correlated with days in the hospital, days in intensive care unit (ICU), and markers of coagulation, indicating associations between ectonucleotidases and disease progression. Similarly, CD39 messenger RNA (mRNA) as upregulated in peripheral blood leukocytes in association with higher soluble CD39 levels in severe COVID‐19 patients, which were related to the length of hospital day and ICU admission (Díaz‐García et al, 2022 ). Furthermore, upregulation in CD39 expression in late‐stage COVID‐19 was associated with heightened levels of STAT‐3 and HIF‐1α, but decreased levels of CD39‐antisense RNA, possibly a purinergic imbalance that contributes to metabolic changes and T‐cell dysfunction (Wang, Veurich, Kalbasi, Shaefi, et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CD39 messenger RNA (mRNA) as upregulated in peripheral blood leukocytes in association with higher soluble CD39 levels in severe COVID-19 patients, which were related to the length of hospital day and ICU admission (Díaz-García et al, 2022). Furthermore, upregulation in CD39 expression in late-stage COVID-19 was associated with heightened levels of STAT-3 and HIF-1α, but decreased levels of CD39-antisense RNA, possibly a purinergic imbalance that contributes to metabolic changes and T-cell dysfunction (Wang, Veurich, Kalbasi, Shaefi, et al, 2021).…”
Section: In Vitro Adenosine Treatment Reduces Nuclear Factor-κb (Nf-κ...mentioning
confidence: 99%
“…Purinergic signaling molecules, such as eATP and eADP bind to P2Y 12 on platelets and induce platelet aggregation and coagulation. Hypoxia- and viral-induced increased CD39 expression on T cells and NK cells in COVID-19 patients with pneumonia was observed by Díaz-García and colleagues ( 180 ). Moreover, soluble active CD39 (sCD39) levels in plasma of COVID-19 patients was associated with longer hospitalisation times, necessity of mechanical ventilation, ICU admission, and death, suggesting sCD39 as a marker for disease severity in COVID-19 patients.…”
Section: The Pathophysiological Influence Of Platelet-net Interplay I...mentioning
confidence: 60%
“…Moreover, soluble active CD39 (sCD39) levels in plasma of COVID-19 patients was associated with longer hospitalisation times, necessity of mechanical ventilation, ICU admission, and death, suggesting sCD39 as a marker for disease severity in COVID-19 patients. Elevated eATP and eADP, as well as decreased adenosine plasma levels may be responsible for increased sCD39, with eATP activating the NLRP-3 inflammasome and eADP activating the procoagulant P2Y 12 receptor on platelets ( 180 ).…”
Section: The Pathophysiological Influence Of Platelet-net Interplay I...mentioning
confidence: 99%
“…We observed that BK1-8 was positively and significantly related to inflammation, suggesting a potential role of this peptide in inflammation in patients with COVID-19. Interestingly, inflammatory condition of patients with COVID-19 has been related to NLRP3 inflammasome (30)(31)(32)(33). Further study of the KKS is quite interesting, especially in the context of thromboinflammation and pulmonary edema complications; in fact, therapeutical targeting on this pathway has been addressed (15).…”
Section: Discussionmentioning
confidence: 99%